The Influence of Work Motivation, Job Satisfaction and Work Discipline on Teacher Performance at SMAN 3 Medan - Siti Humairah; Muhammad Toyib Daulay; Kholilul Kholik (Universitas Dehasen Bengkulu, 2026)
This study aimed to examine the influence of work motivation, job satisfaction, and work discipline on the performance of teachers at SMA Negeri 3 Medan. Specifically, the research investigated whether each variable individually exerts a positive and significant effect on teacher performance, as well as whether the three variables collectively contribute to performance in a positive and significant manner. The study employed a quantitative associative approach, and the data were processed using SPSS. Multiple linear regression analysis was applied to test the proposed relationships. The research involved 70 respondents as the sample. The findings revealed that work motivation has a positive and significant partial effect on teacher performance. Likewise, job satisfaction and work discipline were each found to have a positive and significant individual effect on teacher performance. In addition, the simultaneous test indicated that work motivation, job satisfaction, and work discipline together have a positive and significant influence on the performance of teachers at SMA Negeri 3 Medan.